Efektivitas Terapi Antikoagulan terhadap Parameter Koagulasi pada Pasien Stroke Iskemik: Studi Retrospektif di RSUP Dr. M. Djamil Padang - Suci Wulansari; Dedy Almasdy; Najmiatul Fitria (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Ischemic stroke is a major cause of global morbidity and mortality, with anticoagulant therapy being the primary choice for secondary prevention in specific cases. However, scientific evidence regarding the effectiveness of anticoagulant therapy in the Indonesian population remains limited. Objective: To evaluate the effectiveness of anticoagulant therapy based on changes in coagulation parameters (PT, APTT, INR) and their association with clinical outcomes in ischemic stroke patients at Dr. M. Djamil General Hospital, Padang. Methods: This retrospective analytical observational study included 68 ischemic stroke patients who received anticoagulant therapy (January–December 2024). Effectiveness was assessed by changes in PT, APTT, and INR before and after treatment using Wilcoxon and Kruskal-Wallis tests. Results: Anticoagulant therapy significantly increased PT, APTT, and INR values in most treatment groups (p<0.05), with no significant differences among anticoagulant types (p>0.05). Patients with mortality outcomes showed higher increases in coagulation parameters, but a significant association was only found for changes in APTT (p=0.033). Conclusion: Anticoagulant therapy effectively affects coagulation parameters in ischemic stroke patients, and increased APTT after therapy is associated with mortality. Further prospective studies are needed to confirm these findings.